Novel Rotational Combination Regimen of Skin Topicals Improves Facial Photoaging: Efficacy Demonstrated in Double-Blinded Clinical Trials and Laboratory Validation - DiNatale, Lisa; Idkowiak-Baldys, Jolanta; Zhuang, Young; Gonzalez, Anthony; Stephens, Thomas J.; Jiang, Lily I.; Li, Weiping; Basson, Rubinder; Bayat, Ardeshir (Frontiers in Medicine, 2021)
Topical antiaging products are often a first-line intervention to counter visible signs of facial photoaging, aiming for sustained cosmetic improvement. However, prolonged application of a single active topical compound was observed clinically to lead to a plateau effect in improving facial photoaging. In view of this, we set out to reduce this effect systematically using a multi-tiered approach with laboratory evidence and clinical trials approach. The objectives of the study were to evaluate the effects of active topical ingredients applied either alone, in combination, or in a rotational manner on modulation of facial photoaging. The study methodology included in-vitro, organotypic and ex-vivo skin explants, in vivo biopsy study as well as clinical trials. We demonstrate for the first time that a pair of known antiaging ingredients applied rotationally, on human dermal fibroblasts maximized pro-collagen I production. Indeed, rotational treatment with retinol and phytol/glycolic acid (PGA) resulted in better efficacy than application of each active alone as shown by explants and in vivo biopsy study, with penetration of actives confirmed by Raman-spectroscopy. Furthermore, two split-face, randomized, double-blinded clinical trials were conducted, one for 12-months to compare treated vs. untreated , the other for 6 months followed by a 2-month regression to compare treated vs. commercially-marketed products. In both studies, rotational regimen showed superior results to its matching comparison as assessed by clinical grading and image analysis of crow’s feet wrinkles. In conclusion, rotational regimen using retinol and PGA is effective in treating facial photoaging signs with long-lasting benefits.